2020
DOI: 10.1140/epjds/s13688-020-00227-w
|View full text |Cite
|
Sign up to set email alerts
|

Success and luck in creative careers

Abstract: Luck is considered to be a crucial ingredient to achieve impact in all creative domains, despite their diversity. For instance, in science, the movie industry, music, and art, the occurrence of the highest impact work and of a hot streak within a creative career are very difficult to predict. Are there domains that are more prone to luck than others? Here, we provide new insights on the role of randomness in impact in creative careers in two ways: (i) we systematically untangle luck and individual ability to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 45 publications
1
53
5
Order By: Relevance
“…publications, grants, etc.) would be insufficient (Haslam & Koval, 2010;Hegarty & Walton, 2012;Janosov, Battiston, & Sinatra, 2020;Liu et al, 2018;Nosek et al, 2010;Pluchino, Biondo, & Rapisarda, 2018;Sinatra, Wang, Deville, Song, & Barabási, 2016). This gets even more difficult for an entry-level disconnected psychologist given the absence of the quality indicators (e.g.…”
Section: Disconnected Psychologist In a Psychology Departmentmentioning
confidence: 99%
“…publications, grants, etc.) would be insufficient (Haslam & Koval, 2010;Hegarty & Walton, 2012;Janosov, Battiston, & Sinatra, 2020;Liu et al, 2018;Nosek et al, 2010;Pluchino, Biondo, & Rapisarda, 2018;Sinatra, Wang, Deville, Song, & Barabási, 2016). This gets even more difficult for an entry-level disconnected psychologist given the absence of the quality indicators (e.g.…”
Section: Disconnected Psychologist In a Psychology Departmentmentioning
confidence: 99%
“…Besides predicting song success, music-related data are also relevant to AIbased talent identification, mainly through popularity peaks within artist careers. Such peaks are commonly grouped into hot streak periods, defined as the continuous periods of success or productivity above normal [Liu et al 2018, Garimella and West 2019, Janosov et al 2020. Indeed, identifying hot streaks is very useful for the music industry, as it is one way of investing in the right artist at the most relevant moment.…”
Section: Introductionmentioning
confidence: 99%
“…However, many recent studies have shown that talent does not vary so widely among people and that its probability distribution is limited and concentrated around a well defined mean value. [1][2][3][4] Although individual talents do not differ that much from one person to another one, only a few reach the top. We experience it in many fields [4][5][6][7] and clearly in sports 3,8 , where we observe how people suddenly get notoriety and often huge amounts of money when they win.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Although individual talents do not differ that much from one person to another one, only a few reach the top. We experience it in many fields [4][5][6][7] and clearly in sports 3,8 , where we observe how people suddenly get notoriety and often huge amounts of money when they win.…”
Section: Introductionmentioning
confidence: 99%